Integration of STEM Approach in Science Education: Enhancing Students' Critical Thinking, Creativity, and Engagement in Elementary Schools in Palembang - Esti Susiloningsih; Apit Fathurohman; Siti Dewi Maharani; M. Fatih Fathurohman; Suratmi; Dwi Cahaya Nurani (Postgraduate, University of Mataram, 2025)
This study investigates the impact of STEM (Science, Technology, Engineering, and Mathematics) approaches on enhancing critical thinking, creativity, and student engagement in science education among elementary school students in Palembang, Indonesia. A quasi-experimental design with a pretest-posttest control group was employed, involving 120 fifth-grade students from two public elementary schools. The experimental group participated in a 6-week STEM-based science learning program, which included hands-on activities, project-based learning, and collaborative problem-solving tasks, while the control group followed the conventional science curriculum. Data were collected through pre- and post-tests, creativity assessments using the Torrance Test of Creative Thinking (TTCT), observation sheets, and student project evaluations. The results revealed significant improvements in critical thinking (M=85.6, SD=4.2) and creativity (M=82.4, SD=3.8) among students in the experimental group compared to the control group (critical thinking: M=72.3, SD=5.1; creativity: M=68.7, SD=4.5), with p-values of 0.001 and 0.002, respectively. Additionally, observational data indicated higher levels of student engagement, collaboration, and enthusiasm in the experimental group. These findings underscore the effectiveness of STEM-based learning in fostering higher-order thinking skills and innovation, while also highlighting the importance of contextualizing STEM education to local environments. However, challenges such as limited resources, inadequate teacher training, and rigid curricula were identified as barriers to implementation. The study concludes with recommendations for policymakers and educators to invest in STEM infrastructure, provide professional development for teachers, and reform curricula to support the integration of STEM approaches in Indonesian elementary schools.